A Simple Micro-Model of Market Dynamics. Part I: the "Large Market" Deterministic Limit - Giulio Bottazzi (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
We present a simple agent based model aimed at the qualitative description of trading activity in a stylized financial market. A two assets economy is considered, with a bond providing a riskless constant return and a risky stock, paying constant dividends, whose price is fixed via Walrasian auction. The market participants are speculators described as myopic utility maximizers provided with limited forecasting ability. If one varies the parameters describing the market and the agents behavior, the model presents many distinct phases. In particular, the no-arbitrage fundamental price can emerge as a stable fixed point, while for different parameterizations the market shows chaotic dynamics with speculative bubbles and crashes.
Keywords: 330